Evaluation of Deltamethrin in Combination of Piperonyl Butoxide (PBO) against Pyrethroid Resistant, Malaria Vector, Anopheles stephensi in IRS Implementation: an Experimental Semi-Filed Trial in Iran - Fatemeh Nikpour; Hassan Vatandoost; Ahmad Ali Hanafi-Bojd; Ahmad Raeisi; Mansour Ranjbar; Ahmad Ali Enayati; Mohammad Reza Abai; Mansoreh Shayeghi; Abdol Rasoul Mojahedi; Abolghasem Pourreza (Journal of Arthropod-Borne Diseases, 2017)
Background: The aim of this study was to evaluate different concentrations of deltamethrin combined with formulated piperonyl butoxide (PBO) synergist on various surfaces against the wild strain of Anopheles stephensi, the main malaria vector in Southern Iran under semi-field condition. Methods: Four concentrations of deltamethrin WG 25% (Tagros) and PBO 800EC-UV (Endura) were prepared and sprayed on the pre-designed surfaces in accordance with WHO alliance line of the IRS Micronair®. The WHO’s recommended bioassay kit and method was used during this study. Results: Comparing the mortality rate of mosquitoes, the results showed a significant difference between months after treatment of IRS (Indoor Residual Spraying) (P< 0.05) but didn’t show any significant differences between days during the first and second months (P> 0.05).Statistical test revealed a significance difference between mortality rate of mosquitoes in exposing to concentrations of 1 and 4 (P< 0.05) which demonstrated effect of synergizing PBO on mortality rate. Conclusion: This research as the first semi-field trial on deltamethrin added to different concentrations of formulated PBO for IRS, indicates that deltamethrin+10X PBO is more effective than other concentrations. Therefore, using synergists can be suggested as a new tool for prevention of pyrethriod resistance, although more studies are recommended.